Pengaruh Penerapan E-Sytem Perpajakan Dan Pengetahuan Perpajakan Terhadap Kepatuhan Wajib Pajak Orang Pribadi: Studi Kasus pada Kantor Pelayanan Pajak Pratama Yogyakarta - Veronika Dayat (Jurnal Literasi Akuntansi, 2022)
This study aims to determine whether the e-system of taxation and knowledge of taxation partially or simultaneously affect the obligations of individual taxpayers. The population of this study is all individual taxpayers registered at KPP Pratama Yogyakarta. The total sample is 112 respondents. The sampling technique used is probability sampling. The data collection method used is the questionnaire method. Data processing using SPSS version 22 program. The results of this study indicate that the e-system of taxation partially has a positive effect on individual taxpayer compliance. Tax knowledge partially has a positive effect on individual taxpayer compliance.